PENILAIAN TINGKAT KESEHATAN LEMBAGA PERKREDITAN DESA DENGAN METODE CAMEL PLUS DI LPD TANJUNG BUNGKAK - Wardanthi Kusuma; Sukarnasih Desak (Jurnal Ilmiah Manajemen & Bisnis, 2017)
ABSTRACT Village Credit Institutions is one of Microfinance Institutions are growing rapidly in the province of Bali and is one of the institutions that are at the level of village customs. The standard for assessing the health level has been determined by Bali Governor Regulation No. 11 Year 2013 on a quantitative approach over five (5) factors that affect the condition and development of financial institutions, the Capital, Assets Liquidity, Management, Earning and Liquidity. Besides these five factors, overshooting the lending limits are also taken into account as a reduction of the total value of health outcomes.Based on the discussion that has been described in previous chapters, it can be concluded that the rating of the capital factor results obtained from the CAR ratio was 19.79%, with a credit score of 100%, which is still relatively healthy. Factor is the ratio KAP Earning Assets was 0.20%, with a credit score of 100% and CPRR ratio was 130.83%, with a credit score of 100%, which is still relatively healthy. Assessment management factor of 25 questions or statements of general management and risk management 85 values obtained are still relatively healthy. The earnings factor is the assessment of the ROA ratio was 3.13%, with a credit score of 100% and ROA ratio was 77.71% with 89.16% credit scores are still relatively healthy. Liquidity factor is the ratio of liquid assets was 31% with a credit score of 100% and the LDR is 71.46% with a credit score of 100% were classified as healthy. Rate the latter is the calculation of the legal lending limit in 2015 is not a violation of the legal lending limit. Complications health assessment results in 2015 were awarded with 97.4% categorized as "healthy".